Challenging Traditional Islamic Authority: The Impact of Social Media in Indonesia - Nadirsyah Hosen (Proceedings of International Conference on Da'wa and Communication, 2019)
Islamic teaching is, in fact, the product of a very slow and gradual process of interpretation of the Qur’an and the collection, verification and interpretation of the Hadith during the first three centuries of Islam (the seventh to the ninth centuries AD). This process took place amongst scholars and jurist who developed their own methodology for classification of sources, derivation of specific rules from general principles, and so forth. The traditionalist approach of learning Arabic, for instance, take years to complete and memorising the Arabic grammar takes a long time. Traditionalist Islamic institutions such as pesantren and madrasah produce Kiai, or Muslim clergy and scholars that inevitably create an elite group of scholars. They become the authority who determine the correct interpretation of the Holy books. However, in the era of the social media, such traditional authority has been challenged. Anyone could become a scholar of Islam and to criticise the Kiai harshly. My presentation will critically evaluate this new situation faced by the Indonesian Muslim scholars and to discuss the roots of the problems.